NÅR KULTUREN GÅR I KROPPEN: „Halve grønlændere" som begreb og fænomen - Sørensen, Bo Wagner (Tidsskriftet Antropologi, 1997)
Bo Wagner Sørensen: When Culture Gets Embodied: The Notion and Phenomenon of Greenlandic “Halfies’’ The article tries to make sense of the notion of Greenlandic “halfies” by showing how the notion is part of a cultural discourse which is expressed in terms of “between two cultures”. This discourse points both to people being split between cultures and to the cultures having materialized themselves in individual bodies. In light of recent critique of the concept of culture in anthropology it is reasonable to question the essentialism underlying the expression “between two cultures”, and also to imagine that individuals who invoke it are suffering from “false consciousness”. However, it seems that the discourse causes real pain in actual bodies, and therefore it needs to be taken seriously. In the article, the discourse is put in a larger historical, social and political perspective, showing how the idea has been established that Greenlandic and Danish culture and identity are rather incompatible entities. The Greenlandic struggle for political independence has been fought to a large degree in the field of culture, which implies that people in general are informed by dichotomy thinking. Individuals who do not match up with the acknowledged criteria for Greenlandic culture and identity are inclined to be caught between cultures and loyalities, the result being that the political cultural war is reproduced and reflected in individual bodies. Due to the widespread identityhealth model according to which the ideal identity is a clear-cut and fixed ethnic identity, these individuals are often believed to experience identity crises. The article suggests that the “problem” may not be one of incompatible cultural essences, though it is widely thought so, but rather that culture and identity get politicized.